Fiscal Rules and the Procyclicality of Fiscal Policy in the Developing World - Bova, Elva.; Carcenac, Nathalie; Guerguil, Martine (Washington, D.C. : International Monetary Fund, 2014)
This paper documents the spread of fiscal rules in the developing world and investigates the relation between fiscal rules and procyclical fiscal policy. We find that, since the early 2000s, developing countries outnumbered advanced economies as users of fiscal rules. Rules were adopted either as part of the toolkit to join currency unions or to strengthen fiscal frameworks during and after large stabilization and policy reform episodes. The paper also finds that the greater use of fiscal rules has not shielded these countries from procyclicality, since fiscal policy remains procyclical following the adoption of a fiscal rule. We find partial evidence that some features of 'second generation' rules, such as the use of cyclically-adjusted targets, well-defined escape clauses, together with stronger legal and enforcement arrangements, may be associated with less procyclicality.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet